Anesthesia, Sedation, and Unplanned Extubation of Tracheal Intubation in Children with Severe Pneumonia. (18th October 2021) - Wang, Zengchun; Chen, Qiang; Yu, Lingshan; Huang, Yu; Cao, Hua
Abstract : We randomly divided 200 children with severe pneumonia who met the indications for tracheal intubation into 2 groups in this prospective study. One group that received dexmedetomidine for sedation was recorded as the dexmedetomidine group ( n = 100), and the group that received midazolam for sedation was recorded as the midazolam group ( n = 100). We compared the anesthesia sedation scores, time to fall asleep, time to wake up from anesthesia, related hemodynamic parameters, and adverse reactions between the two groups of children. The failure mode and effect analysis method (FMEA) was also used to investigate the causes of unplanned extubation (UEX) of tracheal intubation in 32 children with severe pneumonia. Our conclusion is as follows: (1) Compared with midazolam, the comprehensive effect of dexmedetomidine on children with severe pneumonia undergoing tracheal intubation for anesthesia and sedation is better, it can effectively shorten the anesthesia induction time and the recovery time after stopping the drug, and there are few adverse reactions, which is worthy of application and promotion. (2) UEX is an important risk factor in the monitoring and nursing of children with severe pneumonia tracheal intubation, and the nursing method of PDCA cycle management is particularly important for them.